Produção de cebola fertirrigada com biofertilizante associado à adubação mineral - Silva, Amison de Santana (Universidade Federal Rural do Semi-Árido, 2012)
In the state of the Rio Grande do Norte called as New border of the onion production , the more expressive plantation of form is relatively recent, and was motivated by the highest prices of the last years. Some producers of fruits and vegetables of the state, already use biofertilizers or liquid manure, as more it is known in the region. The application in the onion if of the one through the irrigation water daily, in the levels varying 50 of 30 L ha-1. The objective of this work was to evaluate the performance of the culture of the onion with the use of biofertilizers associates the mineral fertilizers applied through fertirrigation, in the Mossoró-RN. For in such a way an experiment was lead, in horta didactic of the Departmento de Ciências Vegetais da UFERSA in Mossoró-RN, in the period of September of 2011 the January of 2012. The experimental design was randomized complete block, with four repetitions in factorial project 3 x 3 + 2. The treatments had consisted of the combination of three levels of biofertilizers (15, 30 and 60 L/ha/day) and three levels of fertilization (25, 50 and 100% of the fertilization recommended for Cavalcanti (1998) and two treatments you add (the first one, the application of 100% of the mineral fertilization, following the recommendation of Cavalcanti, (1998) without biofertilizers and as only the application of biofertilizers in the 30 L/ha/day). The combination of the 60 doses L/ha/day of biofertilizers and 75% of the mineral fertilization promoted the biggest values for total, commercial productivity and dry mass of the bulb. The biggest not commercial productivity and average mass of the bulb had been reached with the absence of biofertilizers and 50% of the mineral fertilization. The lesser rubbish percentage was observed with levels 30 L/ha/dia of biofertilizers and 50% of the mineral fertilization. The texts of N, K, Here, Mg, Mn and Fe had been below of the recommended one for excellent development of the culture. The P and An plant was the only nutrient above of the value recommended for the onion
Production of onion fertirrigation with biofertilizers associated with the mineral fertilization
Keywords: Onion; Allium Cepa; Biofertilizers; Nutrition onion; Cebola; Allium Cepa; Biofertizante; Nutrição da cebola; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA